Vermiculitas organofuncionalizadas como adsorventes e sistemas de liberação de fármacos - Avelino, Mirella Cabral (2013)
In this work sodium vermiculite (VNa+) was subjected to controlled acid leaching with nitric acid (HNO3) at concentrations of 0.3 and 1.0 mol/dm3, leading to the solids named V0,3 and V1,0. Sodium vermiculite and activated solids interacted covalently with silane 3- chloropropyltrimethoxysilane, forming the solids VNaCl, V0,3Cl and V1,0Cl and subsequently with aliphatic diamines 1,2-ethylene-(en), 1,4-butil- (but) e 1,6-hexildiamine. The Solids were characterized by CHN elemental analysis, X-ray diffraction, absorption spectroscopy in the infrared region, thermogravimetric analysis and zeta potential measurements. The obtained materials were used for adsorption of the drugs amiloride and ranitidine in aqueous solution. The saturation time for the drugs studied was greater than 200 minutes. The kinetic study showed a good fit to the pseudo-second-order kinetics, with linear coefficients around 0.99 and good agreement between the values of qt and qe. The concentration isotherms showed a multilayered adsorption, with a better linearization for the model proposed by Freudlich, whose best anchoring values were found for the solids V0,3en and V1,0en, with values close to 95 mg/g for amiloride and 80 mg/g for ranitidine. The matrices V0,3hex and V1,0hex were efficient systems for drug release.